2009
DOI: 10.1901/jaba.2009.42-425
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Three Descriptive Methods: Implications for Behavioral Assessment

Abstract: This study compared the outcomes of three descriptive analysis methods-the ABC method, the conditional probability method, and the conditional and background probability method-to each other and to the results obtained from functional analyses. Six individuals who had been diagnosed with developmental delays and exhibited problem behavior participated. Functional analyses indicated that participants' problem behavior was maintained by social positive reinforcement (n = 2), social negative reinforcement (n = 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 12 publications
4
35
1
1
Order By: Relevance
“…It is worth noting that the results of the current study are inconsistent with published research that has employed descriptive assessments of physical activity (e.g., Brown et al, 2009), which suggests that contexts that include fixed equipment produce lower levels of MVPA than outdoor toys and open space. The lack of correspondence between descriptive analyses and experimental analyses of problem behavior has been reported in the literature (e.g., Pence, Roscoe, Bourret, & Ahearn, 2009), but a direct comparison of physical activity assessment methods is needed before any firm conclusions can be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the results of the current study are inconsistent with published research that has employed descriptive assessments of physical activity (e.g., Brown et al, 2009), which suggests that contexts that include fixed equipment produce lower levels of MVPA than outdoor toys and open space. The lack of correspondence between descriptive analyses and experimental analyses of problem behavior has been reported in the literature (e.g., Pence, Roscoe, Bourret, & Ahearn, 2009), but a direct comparison of physical activity assessment methods is needed before any firm conclusions can be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Hall, 2005). Similarly, a number of studies have demonstrated that the outcomes of descriptive analyses rarely match the outcomes of functional analyses (Hall, 2005;Lerman & Iwata, 1993;Mace & Lalli, 1991;Pence, Roscoe, Bourret, & Ahearn, 2009;Piazza et al, 2003;St. Peter et al, 2005;Thompson & Iwata, 2007).…”
mentioning
confidence: 99%
“…Tem sido evidenciada a importância de procedimentos de análise funcional experimental para o embasamento de planejamentos eficazes de intervenções de tratamento baseado em evidências para o SIB (Dixon, Vogel, & Tarbox, 2012; em contraposição a estudos que demonstraram a menor eficácia de métodos indiretos ou descritivos de avaliação funcional (Alter, Conroy, Mancil, & Haydon, 2008;Lang et al, 2009;Pence, Roscoe, Bourret, & Ahearn, 2009;Sasso et al, 1992;Tarbox et al, 2009;Thompson & Iwata, 2007). O presente estudo atingiu seu propósito ao demonstrar a efetividade de procedimentos de reforçamento não contingente e treino de mando planejados com base nos resultados de uma análise funcional experimental, visando à redução do SIB em um indivíduo com deficiência severa.…”
Section: Discussionunclassified